The Influence of Financial Goal on Financial Behavior, Goal Setting Theory Approach - Kemal Arif Rahman; Nur Rahmah Tri Utami (Cita konsultindo, 2024)
The purpose of this study is to investigate the impact of having financial goals on financial behavior, where this relationship is influenced by goal commitment and financial self-efficacy. The research method employs a quantitative approach by distributing questionnaires to 242 respondents residing in Java and having financial goals. Data analysis was conducted using PLS-SEM with the SmartPLS 4.1.0.6 software. The study's findings indicate that social influence positively affects financial behavior. The financial goal difficulty negatively affects financial behavior. The financial goal specificity does not significantly affect financial behavior. Financial self-efficacy does not moderate the effect of goal specificity on financial behavior. Commitment level to the financial goal also does not moderate the relationship between goal difficulty and financial behavior.